PERAN MEDIA PENYIARAN DAERAH DALAM MEMPROMOSIKAN BANDA SEBAGAI PUSAT DESTINASI WISATA MALUKU - Alfredo, Ronald; Sopacua, Yustina; Sahetapy, Rikar (Departemen Ilmu Komunikasi Universitas Andalas, 2024)
This article discusses the important role of regional broadcast media in promoting Banda as a center for Maluku tourist destinations. Banda, an island in Maluku Province, Indonesia has a rich history and stunning natural beauty. However, Banda is often not widely known as a tourist destination. Therefore, this study aims to explore the potential of regional broadcast media in raising Banda's profile as an attractive tourist destination, as well as identifying effective strategies that can be used by regional broadcast media to promote this tourist destination. The research method used is a qualitative method with an in-depth interview approach to regional broadcast media stakeholders and the local government. The research results show that regional broadcast media play a significant role in promoting Banda. Regional broadcasting media acts as an information provider, shows a positive image of Banda, connects the government and the community, and plays a role in educating and empowering the community regarding this tourist destination. The results of the study show that regional broadcast media play a crucial role in promoting Banda as a center for Maluku tourist destinations. Broadcast media, such as radio and television, have a wide coverage and can reach a wider audience. Through special programs and coverage presented, broadcast media can provide significant exposure to the beauty and uniqueness of Banda as a tourist destination. In this case, broadcast media can provide live coverage of tourist attractions, local culture, culinary specialties, and various activities carried out in Banda.